PENGARUH CELELEBRITY ENDORSER DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN MELALUI BRAND TRUST (Studi pada Pengguna Honda Vario di Kawedanan Pedan Kabupaten Klaten) - Ismi Rahmawati; Wida yanto (Universitas Diponegoro, 2022)
Abstract: PT Astra Honda Motor has experienced rapid development which can be proven from the various awards received by PT Astra Honda Motor. However, when viewed from the sales data of PT Astra Honda Motor Klaten, the sales volume decreased by 15.33% in 2016. This type of research is explanatory research, using a questionnaire as a method of data collection. The purpose of this study was to determine the effect of variables Celebrity endorser and Brand Image on Purchasing Decisions through Brand Trust as an intervening variable (Studies on the community in Kawedanan Pedan, Klaten Regency, who use Honda Vario). The research techniques used is Non Probability Sampling, with the type of purposive sampling and snowball sampling. The samples collected were 100 respondents from the Kawedanan Pedan community of Klaten Regency using Honda Vario. Based on the results of data processing analysis with Warp.PLS 7.0, it explains that the celebrity endorser variable, brand image and brand trust have a direct effect on purchasing decisions. And the variable that has the biggest influence is brand image on brand trust. It can also be seen that celebrity endorsers and brand image have an indirect effect on purchasing decisions through brand trust. Researchers advise Astra Honda Motor based on the lowest recapitulation value given by respondents on the assessment indicators, namely by improving and improving, among others, looking at the experience of prospective endorsers before being selected as celebrity endorsers, increasing the attractiveness of advertisements so that potential consumers are interested in the products offered and choose celebrity endorser that suits market needs Keywords: Celebrity Endorser, Brand Image, Brand Trust, Purchase Decision